Unwanted caesarean sections among public and private patients in Brazil: prospective study. Issue 7322 (17th November 2001) - Potter, Joseph E; Berquó, Elza; Perpétuo, Ignez H O; Leal, Ondina Fachel; Hopkins, Kristine; Souza, Marta Rovery; de Carvalho Formiga, Maria Célia
Abstract: Objective: To assess and compare the preferences of pregnant women in the public and private sector regarding delivery in Brazil. Design: Face to face structured interviews with women who were interviewed early in pregnancy, about one month before the due date, and about one month post partum. Setting: Four cities in Brazil. Participants: 1612 pregnant women: 1093 public patients and 519 private patients. Main outcome measures: Rates of delivery by caesarean section in public and private institutions; women's preferences for delivery; timing of decision to perform caesarean section. Results: 1136 women completed all three interviews; 476 women were lost to follow up (376 public patients and 100 private patients). Despite large differences in the rates of caesarean section in the two sectors (222/717 (31%) among public patients and 302/419 (72%) among private patients) there were no significant differences in preferences between the two groups. In both antenatal interviews, 70-80% in both sectors said they would prefer to deliver vaginally. In a large proportion of cases (237/502) caesarean delivery was decided on before admission: 48/207 (23%) in women in the public sector and 189/295 (64%) in women in the private sector. Conclusions: The large difference in the rates of caesarean sections in women in the public and private sectors is due to more unwanted caesarean sections among private patients rather than to a difference in preferences for delivery. High or rising rates of caesarean sections do not necessarily reflect demand for surgical delivery.